PENINGKATAN KEMAMPUAN IMAM DAN KHATIB MELALUI PELATIHAN DI KABUPATEN PASAMAN BARAT - Sobhan, Sobhan; Ridho, Muhammad; Ritonga, Mahyudin (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
The mandate of being imam and khatib in Islamic rituals is not an easy affair, so not everyone is able to become imam and khatib, and not everyone who can afford to be entitled to become imam and khatib. This activity is carried out to provide training to the envoys of mosques in West Pasaman to be skilled in carrying out duties as imams and khatib. Activities are carried out with training techniques, the trainees are 27 people.Â The results of the activity are measured in the form of practice, which instructs participants to appear to be imams and khatib at the end of the activity. The result of this activity is that the trainee has the ability to become imam and khatib, the conclusion is based on the results of the practice displayed by participants that they have had correct readings as well as have sufficient verse memorization, in terms of khatib's ability to be known from their ability to deliver sermons in the presence of instructors and speakers.